Crystallization and preliminary X‐ray analysis of the CRP–cAMP–DNA (full length) complex. Issue 5 (22nd May 2013) - Huang, Jing; Liu, Jing; Tao, Wenbing; Yang, Zhenxing; Qiu, Rui; Yu, Shaoning; Ji, Chaoneng
<x xml:space="preserve">Abstract</x> The Escherichia coli cyclic AMP receptor protein (CRP) is a well known transcription activator protein. In this study, CRP was overexpressed, purified and cocrystallized with cAMP and a 38 bp full‐length double‐stranded DNA fragment. The full‐length segment differed from the half‐site fragments used in previous crystallization experiments and is more similar to the environment in vivo. CRP–cAMP–DNA crystals were obtained and diffracted to 2.9 Å resolution. The crystals belonged to space group P3121, with unit‐cell parameters a = b = 76.03, c = 144.00 Å. The asymmetric unit was found to contain one protein molecule and half a 38 bp full‐length double‐stranded DNA fragment, with a Matthews coefficient of 2.62 Å3 Da−1 and a solvent content of 53.14%.